Broadened assessments, health education and cognitive aids in the remote memory clinic - Owens, Andrew P.; Krebs, Christine; Kuruppu, Sajini; Brem, Anna-Katharine; Kowatsch, Tobias; Aarsland, Dag; Klöppel, Stefan (Frontiers in Public Health, 2022)
Abstract: The prevalence of dementia is increasing and poses a health challenge for individuals and society. Despite the desire to know their risks and the importance of initiating early therapeutic options, large parts of the population do not get access to memory clinic-based assessments. Remote memory clinics facilitate low-level access to cognitive assessments by eschewing the need for face-to-face meetings. At the same time, patients with detected impairment or increased risk can receive non-pharmacological treatment remotely. Sensor technology can evaluate the efficiency of this remote treatment and identify cognitive decline. With remote and (partly) automatized technology the process of cognitive decline can be monitored but more importantly also modified by guiding early interventions and a dementia preventative lifestyle